Pendidikan Kesehatan Kanker Paru Pada Remaja Di SMK Muhammadiyah 1 Purbalingga - Novitasari, Dwi; Yantoro, Awal Tunis; Yulianto, Dwi Agus; Puspita, Sindi Dwi; Gunariwati, Rizki; Bella, Reyvina Shalsa; Simangunsong, Sharon Christa; Fujiyama, Sandy; Siregar, Rifqi Zulhazmi (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Introduction: The lungs are the organs where cancer develops; abnormal cellular development occurs from cells in the bronchi. Many sources indicate a strong correlation between smoking habits and the etiology of lung cancer. Nowadays, the habit of smoking has become a normal occurrence among teenagers, which is causing a high incidence of lung cancer. Objective: The purpose of this dedication to the community is to raise knowledge and provide education to adolescents about lung cancer in a comprehensive way. Method: The activities of dedication to this community are carried out with direct approval on Wednesday, June 12, 2024, from 09.00 to 11.00 BGB. The target of this activity is the students of SMK Muhammadiyah 1 Purbalingga, with 28 participants. Submission of material using the lecture/presentation method and question answering using digital media (PPT) and print media, as well as post-test work to determine the level of knowledge of the participants about lung cancer. Result: Based on the survey of SMK Muhammadiyah 1 Purbalingga students, the participants' characteristics can be grouped by age, gender, and history of smoking. There were nine 16-year-olds, 16 17-year-old students, one 18-year-old student, one 19-year-long student, and one 20-year-old student. By sex, there were 17 male students and 11 female students. There was also a student history of smoking: 6 students smoked and 22 did not smoke. Conclusion: The treatment of lung cancer in these teenagers is going smoothly. There was an increase in knowledge among students, as demonstrated by the post-test results, which showed that the knowledge level of the majority of participants was high, with a total of 15 students, an average of 10 students, and a low 3 students.